A Feminist Informed Investigation - Sinno, Hiba (2022)
Over the years, traditional migration theory has failed to address and examine gender-specific experiences around migration but has used a gendered-neutral approach in highlighting the circumstances that drive women to migrate through irregular and illegal means. Addressing the challenges that these women face using an intersectional approach has been used to a minimal degree in migration studies. Such a gap in the field of migration poses predicaments that prevent policymakers, politicians, intergovernmental organizations, and many more in addressing such challenges and being able to devise a plan that specifically targets these women and putting it into action and implementation. In this research work, I draw upon the EU-Turkey deal and how it played a major role in negatively impacting the irregular migrant women, migrating irregularly from Turkey to reach the EU. This work uses intersectionality that has the potential to generate insights around the experiences and challenges these women face as well as revealing the invisible oppressive forces that are affecting them because of their identity. The purpose of this work is to promote a gendered analysis that leads to drafting gender sensitive and responsive policies that address the human rights of marginalized groups that are being violated during irregular migration.